2023
DOI: 10.3390/antiox12091755
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Olive Flounder Processing By-Products as a Source of Functional Ingredients for Muscle Enhancement

Jimin Hyun,
Sang-In Kang,
Sang-Woon Lee
et al.

Abstract: Olive flounder (OF) is a widely aqua-cultivated and recognized socioeconomic resource in Korea. However, more than 50% of by-products are generated when processing one OF, and there is no proper way to utilize them. With rising awareness and interest in eco-friendly bio-materialization recycling, this research investigates the potential of enzymatic hydrolysis of OF by-products (OFB) to produce functional ingredients. Various enzymatic hydrolysates of OFB (OFBEs) were generated using 11 commercial enzymes. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Because muscles are one of the heaviest tissues in an organism, this observation indicates that the inclusion of AMH in the zebrafish diet not only enhanced their exploring behaviors but also contributed to their overall well-being by preventing Dex-induced loss of body weight [49]. These findings align with our previous study, which provided strong evidence for the potential benefits of olive flounder processing by-products in alleviating Dex-induced muscle atrophy in a zebrafish model, emphasizing its role in enhancing muscle health and functionality [50].…”
Section: Discussionsupporting
confidence: 89%
“…Because muscles are one of the heaviest tissues in an organism, this observation indicates that the inclusion of AMH in the zebrafish diet not only enhanced their exploring behaviors but also contributed to their overall well-being by preventing Dex-induced loss of body weight [49]. These findings align with our previous study, which provided strong evidence for the potential benefits of olive flounder processing by-products in alleviating Dex-induced muscle atrophy in a zebrafish model, emphasizing its role in enhancing muscle health and functionality [50].…”
Section: Discussionsupporting
confidence: 89%
“…26170-043) 1% streptomycin and penicillin was used to differentiate the cultured cells at 37 °C and in a 5% CO 2 controlled environment (60915672, Sanyo Electric Co., Ltd., Osaka, Japan) [ 1 , 2 , 3 , 4 ]. DEXA (CAS-No: 50-02-2) concentration was maintained at 10 µM throughout these experiments to determine whether selected enzyme hydrolysates of C. nippona had a significant effect against that in a dose-dependent way [ 25 , 60 , 61 ]. Initially, the C2C12 cells were seeded into the concentration of 1 × 10 5 cells/mL in the DMEM medium.…”
Section: Methodsmentioning
confidence: 99%
“…Mollusks are the second largest category of farmed seafood, accounting for 21% of all global aquaculture production, and oysters represent a key component in the industry [ 23 ]. Few studies have shown the potential of marine shellfish for muscle growth [ 6 , 24 , 25 , 26 ]. Crassostrea nippona is a shellfish that belongs to the class Bivalves, the phylum Mollusks, the order Ostreoida, and the family Ostreidae, and is located in the marine environments of East Asian countries such as Republic of Korea, China, and Japan [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OFBP was prepared according to a previously described method [36] with slight modifications. Briefly, frozen OFB was thawed overnight at refrigerated temperatures (4 • C) and rinsed with water.…”
Section: Preparation Of Olive Flounder By-product Prozyme 2000p Hydro...mentioning
confidence: 99%